Overview of the VI International Conference on Geotechnology, Mining and Rational Use of Natural Resources – GeoTech-VI 2025 - Sanakulov Kuvandik; Mardonov Bakhtiyor; Khurramov Navruzbek; Abrorov Akbar; Kadirov Yorkin; Kovalev Igor (E3S Web of Conferences)
The Overview is devoted to the main results of the VI International Conference “GeoTech-VI 2025” which was held by Navoi State University of Mining and Technologies in Uzbekistan on 2-4 April 2025. It describes the main directions and gives the details about the participants and the proceedings.